Dopamine Receptor D3 Induces Transient, mTORC1-Dependent Autophagy That Becomes Persistent, AMPK-Mediated, and Neuroprotective in Experimental Models of Huntington’s Disease - Diego Luis-Ravelo; Felipe Fumagallo-Reading; Alejandro Febles-Casquero; Jonathan Lopez-Fernandez; Daniel J. Marcellino; Tomas Gonzalez-Hernandez (Cells)
Huntington disease’s (HD) is a neurodegenerative disorder caused by the expansion of a polyglutamine region (PolyQ) within the huntingtin protein (HTT). Mutated huntingtin (mHTT) is cytotoxic, particularly for striatal medium spiny neurons (MSNs), whose degeneration is the hallmark of HD. Autophagy inducers currently available promote the clearance of toxic proteins. However, due to their low selectivity and the possibility that prolonged autophagy hampers essential processes in unaffected cells, researchers have questioned their benefits in neurodegenerative diseases. Since MSNs express dopamine receptors D2 (DRD2) and D3 (DRD3) and DRD2/DRD3 agonists may activate autophagy, here, we explored how healthy and mHTT-challenged cells respond to prolonged DRD2/DRD3 agonist treatment. Autophagy activation and its effects on mHTT/polyQ clearance were studied in R6/1 mice (a genetic model of HD), their wild-type littermates, and DRD2- and DRD3-HEK cells expressing a pathogenic (Q74) and a non-pathogenic (Q23) polyQ fragment of mHTT treated with the DRD2/DRD3 agonist pramipexole. Two forms of DRD3-mediated autophagy were found: a transient mTORC1-dependent in WT mice and Q23-DRD3-HEK cells and a persistent AMPK-ULK1-activated in R6/1 mice and Q74-DRD3-HEK cells. This also promoted a robust clearance of soluble mHTT/polyQ and neuroprotection in striatal neurons and DRD3-HEK cells. The findings indicate that DRD3-induced autophagy may be a safe, disease-modifying intervention in HD patients.